Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content:1. The Effectiveness of Using Some Active Learning Strategies in the Developing of Rhetorical Skills Among First Grade Secondary Students in the Republic of YemenMr. Fouad Hussein Al-Salhi Ahmed2. The Effect of Multiple Intelligences Based Teaching on the Achievement in the Social Studies Course and the Development of Critical Thinking Skills among the Ninth Grade Female Students in the United Arab EmiratesMrs. Raeda Sobhi Youssef Abdullah, Prof. Odeh Abdel-Gawad Abu Sneineh3. Content Analysis of the Fourth Grade Mathematics Curriculum in Palestine in Light of Thinking SkillsDr. Ahmed M. Othman, Dr. Reem M. Jawabreh4. The Impact of Using Prior and Acquired Knowledge Strategy on the Achievement and Acquisition of Scientific Concepts for the Third Basic Grade Students in JordanMrs. Fadia Hassan Nimr Abdel-Rahman, Prof. Ouda Abdel-Gawad Abu Sneineh5. Teacher competencies necessary for teaching chemistry in the context of Twenty-first century skillsMr. Ahmad Mohammed Alamry , Co-Prof. Manal Hassan Bin Ibrahim6. The Degree of Involving Seventh Grade Students in the Content of the English Language Textbook in JordanMr. Rami Mousa Al-Amayreh, Dr. Zuhair Dawood. Zaghlool7. Computer teachers' attitudes towards using Madrasati platform in teaching in Al-Makhwah GovernorateMr. Muteb Abduallh Muteb Alessi
Keywords: Journal of Curriculum and Teaching Methodology